Chemometric study and optimization of heads pace solid-phase microextraction parameters for the determination of multiclass pesticide residues in processed cocoa from Nigeria using gas chromatography/mass spectrometry - Abdulra'uf, L.B.; Guan, H.T. (2014)
Solid-phase microextraction (SPME) is a solventless sample preparation method that combines sample preparation, isolation, concentration, and enrichment into one step. A simple and effective method coupling headspace-SPME to GC/MS was developed for the analysis of chlorpyrifos, fenitrothion, endosulfan I, and endosulfan " pesticide residues in cocoa powder. In this study, multivariate strategy was used to determine the significance of the factors affecting the SPME of the pesticides using a Plackett-Burman design, and the significant factors were optimized using central composite design. The analytes were extracted with 100 pm polydimethylsiloxane fibers according to the factorial design matrix and desorbed into a GC/MS instrument The developed method was applied for the analysis of a cocoa powder sample, and it exhibited good figures of merit for the analytical methodology. Using the optimized conditions, the linearity ranged from 2.5 to 500 pg/kg (R2> 0.99) using an internal standard calibration method, and the average recoveries were between 75 and 95%, with RSD values between 3.8 and 9.7%.